Restoring species‐rich meadow by means of turf transplantation: long‐term colonization of ex‐arable land. Issue 1 (24th November 2016) - Mudrák, Ondřej; Fajmon, Karel; Jongepierová, Ivana; Doležal, Jiří
Abstract: Question: Do transplanted turfs of preserved meadow vegetation enrich ex‐arable land with species and promote meadow restoration? If so, can this ecologically non‐random process be predicted by plant functional traits? Are transplanted turfs stable over time while preserving their high species richness or do they change in composition, for instance, due to weeds expanding from the surrounding ex‐arable land? Methods: In the experiment, 25 meadow turfs 40 cm × 40 cm × 30 cm in size were transplanted to ex‐arable land. Species composition and cover were monitored in the transferred turfs and their surroundings in three 40 cm × 40 cm plots positioned in a row (transplant, adjacent and distant surrounding area) for a period of 12 yrs. Location: Bílé Karpaty Mts., SE Czech Republic. Results: With the turfs, 80 species were transferred, 53 of which were recorded in the turf surrounding ex‐arable land. After 9 yrs, the number of species (on average 16 per plot) did not differ between the turf and its surroundings. Most of these species had been transferred and are typical of the local meadow vegetation, making up most of the plant cover. Weedy species, originally abundant on the ex‐arable land, did not penetrate the turf and retreated with time. The species composition converged between the turf and its surroundings, but it also changed from that of the turf source meadow. This was mainly due to the expansion of the strongly competitive grass Brachypodium pinnatum at the expense of Bromus erectus . The species that spread best to the arable land had a high leaf dry matter content. Species with the best performance in the turf had high ability for lateral clonal spread. Conclusion: Turf transplantation promoted the establishment of target meadow species on ex‐arable land and supported restoration of meadow vegetation, but plant species composition changed from the turf source meadow, and expansion of target species from the turf into the surrounding area required a long time period. Abstract : Transplanted turfs of preserved meadow vegetation enriched ex‐arable land with species and promoted meadow restoration. With the turfs, 80 species were transferred, 53 of which were recorded in the turf surrounding on ex‐arable land. After 9 years, the number of species did not differ between the turf and its surrounding. However, plant species composition changed from the turf source.